Lymph node dissection in thymic carcinomas and neuroendocrine carcinomas. (21st June 2021) - Hamaji, Masatsugu; Omasa, Mitsugu; Nakanishi, Takao; Nakakura, Akiyoshi; Morita, Satoshi; Miyamoto, Ei; Nakagawa, Tatsuo; Miyahara, So; Sonobe, Makoto; Takahashi, Mamoru; Terada, Yasuji; Hijiya, Kyoko; et al.
Abstract: OBJECTIVES: Although lymph node (LN) metastases are not uncommon in thymic carcinomas, preoperative LN evaluation, intraoperative lymph node dissection (LND) and postoperative outcomes remain unknown. The aim of this study was to elucidate the characteristics of and outcomes in patients with thymic carcinomas and thymic neuroendocrine carcinomas undergoing LND. METHODS: A retrospective chart review was performed using our multi-institutional database to identify patients who underwent resection and LND for thymic carcinoma or thymic neuroendocrine carcinoma between 1991 and 2018. An enlarged mediastinal LN was defined as having a short-axis diameter >1 cm. We assessed survival outcomes using the Kaplan–Meier analysis. RESULTS: N1-level LND was performed in 41 patients (54.6%), N2-level LND in 14 patients (18.7%) and both-level LND in 16 patients (21.3%). Pathological LN metastasis was detected in 20 patients (26.7%) among the 75 patients undergoing LND. There was a significant difference in the number of LN stations ( P = 0.015) and metastasis factor ( P = 0.0042) between pathologically LN-positive and pathologically LN-negative patients. The sensitivity of enlarged LNs on preoperative computed tomography was 18.2%. There was a tendency towards worse overall survival of pathologically N2-positive patients, although the difference was not statistically significant ( P = 0.15). CONCLUSIONS: Preoperative CT appears to play a limited role in detecting pathological LN metastases. Our findings suggest that the significance of N1- and N2-level LND should be evaluated in prospective studies to optimize the postoperative management of patients with thymic carcinomas and neuroendocrine carcinomas.